Desenvolvimento de pluviômetro eletrônico de baixo custo - Daros, Rodrigo Fernandes (2019)
The objective of this work was to develop, calibrate, validate and analyze the costs of a reliable electronic rain gauge, which allows obtain continuously the volume, frequency and intensity of rainfall. The research was carried out in three stages: development, calibration and validation. Initially, the user requirements analysis was defined, considering that the used electronic pluviometer is based on a scale system, with a passage sensor coupled to the set, to detect the moment of occurrence of the event of passage of the scale. Thus, it was defined that the system to be developed needs to record date, time and data to be collected in a memory system, be portable for transportation and have autonomy of energy for field use. After that, the modeling of the architecture was done, detailing the photovoltaic cells system (solar panel) that keeps two rechargeable batteries that can load and feed the embedded system, ensuring the system operation and the activation of the microcontroller, waiting to read and record the event of the scale. The equipment support structure was designed to keep the box control accessible, the solar panel in a favorable position for solar radiation incidence and the rain gauge funnel obstaclefree. For the calibration a system capable of produce different water flows was set up, monitoring the collection time to control the rainfall intensities generated in the system; this evaluation was performed to quantify the volume of rain in each tilt. The data were submitted to regression analysis to obtain the formula to be used to quantify rainfall through the number of tilts. The calibration process of the rain gauge presented highly reliable interactions, so its equation could be used to obtain precipitation data collected through the developed rain gauge. The developed rain gauge presented low financial investment in its development when compared to similar ones in the market, showing that the developed equipment can become an accessible tool for small and large producers.